Drying–rewetting cycles and γ-irradiation effects on enzyme activities of distinct layers from a Quercus ilex L. litter - Alarcón-Gutiérrez, Enrique; Floch, Carine; Ziarelli, Fabio; Augur, Christopher; Criquet, Stéven (Soil Biology and Biochemistry, 2010)
In a Mediterranean climate, water stress is one of the principal constraints on proper forest ecosystem functioning. Drought influences rates of organic matter degradation by affecting microbial growth and enzyme activities. The objectives of this study were: (i) to evaluate the effect of repeated dryingerewetting cycles on cellulase, alkaline phosphatase and fluorescein diacetate (FDA) hydrolase activities of three distinct Quercus ilex L. litter layers, and (ii) to investigate the effect of these cycles on γ-irradiated litters in order to distinguish the abiotic influence on the fluctuations observed. Results, for all three layers, showed high correlations between litter water content and enzyme activities. Under mesocosm conditions, and using non-sterilized litter samples, cellulase, alkaline phosphatase, and FDA activities significantly decreased or increased during drying or rewetting cycles respectively. Significant differences were also found when evaluating the effect of litter depth on enzyme activities, the intermediate depth (OLv layer) generally being the most active. For γ-sterilized samples, FDA activity still fluctuated with dryingerewetting cycles. Assays showed that pre-humidification of γ-irradiated litter increased FDA activity two-fold in the first 30 min. All these results have shown that, following dryingerewetting cycles, some of the fluctuations occur independently of microbial growth, suggesting abiotic interactions, such as desorption, in combination with both solvatation status and conformational changes of enzymes.
Keywords: abiotic fluctuations; Drying-rewetting; Enzyme activities; Moisture; γ-Irradiation

Microbial activity and quality changes during decomposition of Quercus ilex leaf litter in three Mediterranean woods - Papa, S.; Pellegrino, A.; Fioretto, A. (Applied Soil Ecology, 2008)
Changes in enzyme activities during litter decomposition provide diagnostic information on the dynamics of decay and functional microbial succession. Here we report a comparative study of enzyme activities involved in the breakdown of major plant components and of other key parameters (microbial respiration, fungal biomass, N, lignin and cellulose contents) in homogeneous leaf litter of Quercus ilex L. incubated in three evergreen oak woods in Southern Italy (Campania), differing for chemical and physical soil characteristics and microclimatic conditions. The results showed that the litter mass loss rates were similar in the three wood sites. Independently of the incubation sites, cellulase, xylanase and peroxydase activities showed seasonal variations with maximum and minimum levels in wet and dry periods, respectively, and this pattern closely matched microbial respiration. Activities of a- and b-amylase, instead, were high at the beginning of incubation and quickly decreased with decomposition progress because their substrate was rapidly depleted. Laccase activity, in contrast, was low at the beginning of incubation but after 6 months it increased signiﬁcantly. The increase of laccase activity was correlated to an increase in fungal biomass, probably reﬂecting a major shift in the litter microbial community. As concerns quality changes, N and lignin content did not signiﬁcantly change during decay. The cellulosic component started being degraded after about 6 months in the litter incubated in two of the three wood sites and from the start of decomposition in the third site. Apart from minor differences in the levels of certain enzyme activities, the data showed that the functional microbial succession involved in the decomposition of Q. ilex leaf litter did not change appreciably in response to differences in soil and microclimatic conditions in the incubation sites.
Keywords: Cellulose; Enzyme activities; Fungal biomass; Lignin; litter decomposition; Microbial respiration

Microbial activity and quality changes during decomposition of Quercus ilex leaf litter in three Mediterranean woods - Papa, S; Pellegrino, a; Fioretto, a (Applied Soil Ecology, 2008)
Changes in enzyme activities during litter decomposition provide diagnostic information on the dynamics of decay and functional microbial succession. Here we report a comparative study of enzyme activities involved in the breakdown of major plant components and of other key parameters (microbial respiration, fungal biomass, N, lignin and cellulose contents) in homogeneous leaf litter of Quercus ilex L. incubated in three evergreen oak woods in Southern Italy (Campania), differing for chemical and physical soil characteristics and microclimatic conditions. The results showed that the litter mass loss rates were similar in the three wood sites. Independently of the incubation sites, cellulase, xylanase and peroxydase activities showed seasonal variations with maximum and minimum levels in wet and dry periods, respectively, and this pattern closely matched microbial respiration. Activities of a- and b-amylase, instead, were high at the beginning of incubation and quickly decreased with decomposition progress because their substrate was rapidly depleted. Laccase activity, in contrast, was low at the beginning of incubation but after 6 months it increased signiﬁcantly. The increase of laccase activity was correlated to an increase in fungal biomass, probably reﬂecting a major shift in the litter microbial community. As concerns quality changes, N and lignin content did not signiﬁcantly change during decay. The cellulosic component started being degraded after about 6 months in the litter incubated in two of the three wood sites and from the start of decomposition in the third site. Apart from minor differences in the levels of certain enzyme activities, the data showed that the functional microbial succession involved in the decomposition of Q. ilex leaf litter did not change appreciably in response to differences in soil and microclimatic conditions in the incubation sites.
Keywords: Cellulose; Enzyme activities; Fungal biomass; Lignin; litter decomposition; Microbial respiration